2006
DOI: 10.1097/01.qai.0000245886.51262.67
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Disoproxil Fumarate, Emtricitabine, and Efavirenz Versus Fixed-Dose Zidovudine/Lamivudine and Efavirenz in Antiretroviral-Naive Patients

Abstract: Over 96 weeks, the combination of TDF, FTC, and EFV was superior to fixed-dose ZDV/3TC + EFV for achieving and maintaining an HIV RNA level <400 copies/mL and an increase in CD4 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(152 citation statements)
references
References 15 publications
14
131
0
7
Order By: Relevance
“…Six efficacious ART regimens, each with decreasing efficacy, are specified in the model. 2734 All patients also face a risk of non-HIV-related mortality that depends on age and sex, 35 adjusted for race/ethnicity and other risk factors as has been previously described. 35–37 Cost of HIV treatment and care is from the health system perspective and is derived from HIV Research Network data and Medicare fee schedules.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Six efficacious ART regimens, each with decreasing efficacy, are specified in the model. 2734 All patients also face a risk of non-HIV-related mortality that depends on age and sex, 35 adjusted for race/ethnicity and other risk factors as has been previously described. 35–37 Cost of HIV treatment and care is from the health system perspective and is derived from HIV Research Network data and Medicare fee schedules.…”
Section: Methodsmentioning
confidence: 98%
“…26 Once initiated on ART, patients have a probability of virologic suppression and subsequent CD4 count gain that is specified based on current literature and divided into 3 time periods, with the greatest benefit occurring in the first 2 months on ART. 27 CD4 count gains are associated with reductions in the risk of developing opportunistic infections and of HIV-related death that also depend on prior history of opportunistic infections and ART treatment status. Upon virologic rebound, patients are switched to the next available ART regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Some clinical studies have found that the dose-skipping frequency increases with the increasing number of daily medicines (17)(18)(19)(20)(21)(22). In such cases, treatment success depends on completely regular medication use.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of whether to use an NNRTI, a boosted PI, or an INSTI as part of initial therapy needs to be individualized, based on issues including co-morbid conditions, likely adherence, dosing requirements, and pregnancy potential. A combination of tenofovir and emtricitabine has become the most commonly used dual-NRTI backbone in the developed world because of superior virologic outcomes, reduced drug resistance, and less toxicity than other NRTI regimens (13,60,64). Combination therapy without a dual-nucleoside backbone is not generally recommended for initial antiretroviral therapy, though several "nucleoside-sparing" regimens are under study.…”
Section: What Regimen To Begin?mentioning
confidence: 99%